Building a transformative partnership between health‐system and community‐based pharmacies. Issue 6 (8th June 2020) - Vest, Mary‐Haston; Clifton, Cody L.; Cochran, Kelly A.; Fish, Hannah M.; Jacobsen, Ryan B.; McDonough, Randal P.; Osterhaus, Matthew C.; Rudder, Catherine M.
Abstract: Purpose: Health‐system pharmacists and community‐based pharmacists have long held professional relationships. However, the success of each group is often not interdependent and aligned. In 2018, the American College of Clinical Pharmacy (ACCP), CPESN USA, and the National Community Pharmacists Association (NCPA) Innovation Center led a meeting to build patient‐centered pharmacist teams to achieve medication optimization across care settings. Seven community pharmacists and health‐system/clinic‐based pharmacist teams participated in this meeting and left with the intentional commitment to build sustainable partnerships. This report describes the establishment of this partnership, and the subsequent application of Guiding Statements for these collaborations. This report also describes both the successes realized and the lessons learned, and to serve as practical recommendations for institutions interested in pursuing similar partnerships. Results: Initial learnings from these partnerships have provided a proof of concept that an intentional approach to the relationship between a health‐system/clinic‐based pharmacist and community‐based pharmacist can lead to improvements in patient care as well as a professional collaboration. We experienced improved communication and closed‐loop care, improved professional relationships across care settings, and enhanced clinical services. However, these partnerships were not without challenges. For instance, lack of interoperability and limited electronic health record access made certain outcomes difficult to track. Conclusion: The purposeful establishment of partnerships between health‐system/clinic‐based pharmacists and community‐based pharmacists, built upon the needs of both entities, allowed institutions to develop an aligned commitment to care for shared patients. Over the initial years of these partnerships, many successes were realized and lessons were learned. Both the successes and the challenges can serve as beneficial resources for institutions interested in developing similar partnerships.